Enhancing EFLStudents’ Writing Proficiency through The Compare-Diagnose-Operate Strategy - Rahmansyah, Habib; Yanti, Khotma; Zarkasih, Ardhiansyah P; Hutasuhut, Lutfiah; Aryani, Kiki (International Journal of English and Applied Linguistics (IJEAL), 2026)
The aims of this research are to know: 1) The extent of application of Compare-Diagnose-Operate (CDO) strategy in teaching writing, 2) The extent of the students’ writing proficiency before and after using CDO strategy, 3) Whether there is significant of using CDO strategy on students’ writing proficiency. This research uses experimental method with the pre-experimental design by using one group pre-test and post-test design. The population is seventh grade students consists 140 students, then uses purposive sampling technique to get the 28 students. In collecting the data, the researcher uses observation sheet and test as the instruments. The use of CDO in teaching writing was  85%, it was “Very Good’’, 2) The extent of the students’ writing proficiency before and after using CDO strategy, it can be seen from the students’ frequency before using CDO strategy was “Unacceptable-not’’ and after using CDO strategy was 72.11 it is categorized “Good to adequate’’, 3) There is a significant effect of using CDO strategy on students’ writing proficiency.